Deutsche Kunst im 20. Jahrhundert : Malerei und Plastik 1905-1985 - Joachimides, Christos M.; Rosenthal, Norman; Schmied, Wieland; Grasskamp, Walter (München : Prestel Verlag, 1986)
Nietzsche, Friedrich ; Kirchner ; Kandinsky ; Nolde, Emil ; Kokoschka, Oskar ; Corinth, Lovis ; Lehmbruck, Wilhelm ; Beckmann, Max ; Schwitters, Max ; Ernst, Max ; Dix, Otto ; Schlemmer, Oskar ; Klee, Paul ; Beuys, Joseph ; etc.
Deutsche Kunst im 20. Jahrhundert : Malerei und Plastik 1905-1985, Staatsgalerie Stuttgart vom 8. Februar bis 27. April 1986
kunstcatalogus
Keywords: Duitsland